Из опыта прогнозирования новых технических решений на конструкцию форвардера - Shegelman I. R. (Innovative technologis in science and education, 2017)
shows the experience of using functional and technological analysis for the synthesis of new technical solutions to improve the design of the forwarder.
Keywords: лесосечные работы; форвардер; forwarder; logging